MIXTURES OF NON-IONIC SURFACTANTS FOR CLEANING COMPOSITIONS - E. F. Bukanova; V. M. Filippenkov; Y. Revina (Тонкие химические технологии, 2017)
The surface behavior and micelle formation of binary and ternary compositions of nonionic surfactants are studied in relation to their cleaning ability with respect to cotton fabric. In mixtures of an alkyl glucoside and oxyethylated alcohol, antagonistic interaction of the components is observed. When a tertiary amine oxide (Oksipav) having a semipolar N→O bond in the molecule is introduced, the formation of mixed micelles occurs. In solutions of mixtures of nonionic surfactants, the critical concentration of micelle formation is reduced, surface activity is increased, the values of maximum adsorption in the surface layers become higher, and the area occupied by the surfactant molecules in a saturated adsorption layer (smol) is reduced as compared to the individual surfactants. Low values of interfacial tension (from 1.2 to 0.88 mJ/m2) in the surfactant solution - toluene system increase the degree of surface cleaning from oil pollution. When cleaning solutions contain mixtures of three nonionic surfactants with different functional groups, synergysm of the wetting, stabilizing, foaming and emulsifying abilities of liquid detergents is provided. Compositions developed on the basis of colloid-chemical criteria are characterized by high removal efficiency with respect to pigment-oil stains from the fabric at pH in the range from 8.8 to 10.5.